Change in Surface Conductivity of Elastically Deformed p-Si Crystals Irradiated by X-Rays - R. Lys; B. Pavlyk; R. Didyk; J. Shykorjak (Nanoscale Research Letters, 2017)
Abstract Changes in conductivity of irradiated and non-irradiated p-Si mono-crystals under the influence of elastic uniaxial mechanical stress were investigated in this paper. An analytical expression was suggested to describe the dependence of surface conductivity as a function of mechanical stress and X-ray irradiation dose. It was shown that 4-angular nano-particles on the surface of “solar” silicon affect the electroconductivity changes under mechanical stress. It was established that X-ray irradiation causes the generation of point defects in silicon. These defects suppress the dislocations movement. It was shown that the resistivity of previously irradiated samples of “electronic” silicon is only slightly sensitive to the influence of uniaxial compression at certain deformation rate.